Energy optimal control of mobile manipulators subject to compensation of external disturbance forces - Galicki, Mirosław (Mechanism and machine theory, 2022)
This study proposes a new class of controllers for mobile manipulators subject to both undesirable forces exerted on the end-effector and unknown friction forces coming from joints directly driven by the actuators as well as undesirable forces resulting from the kinematic singularities appearing on the mechanism trajectory. Based on the suitably defined task space non-singular terminal sliding manifold (TSM) and the Lyapunov stability theory, we derive a class of estimated extended transposed Jacobian controllers which seem to be effective in counteracting the unstructured forces. Due to a redundant nature of the tasks to be accomplished, our controllers also a involve useful criterion function (energy consumption) in optimally tracking a desired trajectory. Moreover, in order to eliminate (or to alleviate) undesirable chattering effects the proposed control laws include second order sliding techniques. The numerical computations, which are carried out for a mobile manipulator consisting of a platform of (2, 0) type and a holonomic manipulator of two revolute kinematic pairs, illustrate the performance of the proposed controllers and simultaneously their minimizing properties. Numerical comparison with other control algorithms well-known in the literature is also given. •We offer the solution of energy optimal robust control of mobile manipulators.•The mobile manipulator is subject to unknown external disturbance forces.•Controllers involve new non-singular TSM manifold to track desired trajectory.•The approach is based on utilizing the sliding techniques of the second order.•Our controllers tackle also singular configurations.